Predictors of student mental health and academic competence - Maretha Visser; Eloise Law-van Wyk; Andries Masenge (Journal of Student Affairs in Africa, 2026)
Promoting tertiary students’ academic success and mental health is increasingly recognised as a critical issue in education. In an effort to develop strategies to promote student success and mental health, an existing dataset was re-analysed to identify predictors of student academic competence and mental health, using the Biopsychosocial Model as a theoretical framework. Cross-sectional data collected from university students (n = 3,239) via an online survey during the COVID-19 pandemic were used. Structural equation modelling used various domains of wellness (physical, emotional, social, spiritual, financial, environmental, intellectual) as well as hope, coping and satisfaction with institutional support to predict mental health and academic competence (as proxy for academic success). Hope, coping and academic competence were the main direct predictors of mental health as well as several domains of wellness (intellectual, spiritual, emotional) through coping as mediator. Intellectual wellness, coping and satisfaction with institutional support were the most important predictors of academic competence. Tertiary institutions can use these findings to plan appropriate resources and services to promote and sustain students’ mental health and academic functioning.